2021
DOI: 10.4103/abr.abr_211_20
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Glycerol/Chitosan/Polyvinyl Alcohol-Based Transparent Hydrogel Films Loaded with Silver Nanoparticles for Antibacterial Wound Dressing Applications

Abstract: Background: Wounds have a bad prognostic nature and excessive discharges whose regular wound dressings are ineffective. Hydrogels are the best candidates for dressing such wounds due to their high water content and ability to exchange substances. Accordingly, the purpose of this study was to make a novel hydrogel wound dressing following the integration of various findings on wound healing and the use of regenerative medicine. Materials and Methods: Various compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…These results are consistent with the gel fraction findings, suggesting a correlation between gel fraction and degradation rate, as expected. Samadi et al showed that the addition of npAg to a glycerol/chitosan/polyvinyl alcohol-based hydrogel significantly decreased the degradation rate [ 91 ], while Qui et al showed that an increase in npAg concentration in a hydroxypropyl methylcellulose-hydroxyapatite scaffold hydrogel leads to an increased degradation rate [ 105 ]. Wassenaar et al investigated how DOXY incorporation affects the degradation rate of an injectable hydrogel derived from decellularized porcine ventricular myocardium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the gel fraction findings, suggesting a correlation between gel fraction and degradation rate, as expected. Samadi et al showed that the addition of npAg to a glycerol/chitosan/polyvinyl alcohol-based hydrogel significantly decreased the degradation rate [ 91 ], while Qui et al showed that an increase in npAg concentration in a hydroxypropyl methylcellulose-hydroxyapatite scaffold hydrogel leads to an increased degradation rate [ 105 ]. Wassenaar et al investigated how DOXY incorporation affects the degradation rate of an injectable hydrogel derived from decellularized porcine ventricular myocardium.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of the hydrogel was assessed using SEM ( Figure 19 ). Increasing magnification and focus led to the destruction of the hydrogel’s surface in some cases, with the appearance of cracks, so the microscope parameters had to be carefully adjusted [ 91 ]. The surface morphology of the hydrogel membranes differs among formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Next generation wound dressings should provide an occlusive wound bed, absorb exudate, and be conformable to the irregular topography of the stratum corneum, while also being transparent to allow for easy inspection by clinicians without removal of the bandage. Additionally, these wound dressings should be cost efficient and avoid the use of relatively expensive doping agents such as silver nanoparticles [13] , dextran [14] and/or chitosan [11] . The biocompatibility, ease of fabrication, cost, absorbing capabilities, and scalability render PVA a promising material for use in a wide array of applications including but limited to scaffold materials [15] , doped hydrogels [16] for pharmaceutical applications [17] , sacrificial layer in fabricating epidermal electronics [18] and as a stand-alone or composite material for wound dressings [11] , [19] [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The biocompatibility, ease of fabrication, cost, absorbing capabilities, and scalability render PVA a promising material for use in a wide array of applications including but limited to scaffold materials [15] , doped hydrogels [16] for pharmaceutical applications [17] , sacrificial layer in fabricating epidermal electronics [18] and as a stand-alone or composite material for wound dressings [11] , [19] [21] . There is a paucity of commercial controls utilized within studies of PVA based wound dressings to provide clinical relevance [13] , [19] , [22] , [23] . Elucidating the mechanical and absorption properties of PVA based on varied glycerol concentrations for the fabrication of a wound dressing has not previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of these traditional antimicrobial agents is related to antibiotic resistance. The alternative to topical antimicrobial agents is to develop new wound healing materials based on alginate [17], chitosan [6,18], collagen [19], nanocellulose [20], inorganic antimicrobial agents such as zinc oxide [5,21], and plant extracts [22].…”
Section: Introductionmentioning
confidence: 99%